2004
DOI: 10.1021/ja0474695
|View full text |Cite
|
Sign up to set email alerts
|

PtCl2-Catalyzed Cycloisomerizations of 5-En-1-yn-3-ol Systems

Abstract: 5-En-1-yn-3-ol substrates bearing a free hydroxyl group or an acyl group are highly versatile partners for PtCl2-catalyzed cycloisomerizations. Electrophilic activation of the alkyne moiety triggers at wish a hydride or an O-acyl migration yielding at the end to regioisomeric keto derivatives. The efficient preparation of Sabina ketone, an important monoterpene precursor, has been worked out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0
8

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(82 citation statements)
references
References 13 publications
3
71
0
8
Order By: Relevance
“…[36] The deuterium label in the product appeared exclusively at the C (2) The studies of Malacria and co-workers are summarized in Scheme 46 and Scheme 47. [37] This work demonstrated that enynes containing terminal alkynes successfully participated in the cycloisomerization process. In addition, the authors established that the formation of bicycloA C H T U N G T R E N N U N G [3.1.0]hexenes was stereospecific.…”
Section: Formation Of Bicycloa C H T U N G T R E N N U N G [310]alkmentioning
confidence: 81%
See 1 more Smart Citation
“…[36] The deuterium label in the product appeared exclusively at the C (2) The studies of Malacria and co-workers are summarized in Scheme 46 and Scheme 47. [37] This work demonstrated that enynes containing terminal alkynes successfully participated in the cycloisomerization process. In addition, the authors established that the formation of bicycloA C H T U N G T R E N N U N G [3.1.0]hexenes was stereospecific.…”
Section: Formation Of Bicycloa C H T U N G T R E N N U N G [310]alkmentioning
confidence: 81%
“…[36,37] These reports were soon followed by a communication from the Toste laboratory, describing a series of independently observed cycloiso- merizations of 1,5-enynes, which were catalyzed by cationic gold-phosphine complexes. [38] Fürstner and co-workers reported that subjection of enyne 200 to a catalytic amount of PtCl 2 in toluene at 60 8C afforded bicyclic ketone 201 in 75 % yield (Scheme 44).…”
Section: Formation Of Bicycloa C H T U N G T R E N N U N G [310]alkmentioning
confidence: 99%
“…Echavarren et al [128] untersuchten speziell Enolether als Alkenpartner in dieser Cycloisomerisierungsreaktion. Die Arbeitsgruppen von Fürstner [129] und Malacria [130] erweiterten die Methode elegant auf 3-hydroxylierte 1,5-Enine. Fürstner [135] beschrieben [Gl.…”
Section: Enin-umlagerungenunclassified
“…Aufgrund von Markierungsexperimenten mit Deuterium [41,138] und DFT-Rechnungen [115,138] Anknüpfend an die Untersuchung der intermolekularen Variante dieser Umwandlung durch Ohe, Uemura und Miki [141] veröffentlichten die Arbeitsgruppen von Fürstner [129] und Malacria [130,142] [130] Durch Erweiterung des Konzepts auf 1,4-Enine haben Sarpong et al [143] …”
Section: Enin-umlagerungenunclassified
“…214 Thus, for example, the gold-catalyzed cyclization of the propargylic acetate in equation (74) gives the product of cyclization and 1,2-acetate migration, which was methanolyzed to yield the corresponding ketone. The first mechanistic pathway in equation (73) is probably followed when n = 2, as shown in a key Pt(II)-catalyzed cyclization for the synthesis of (−)-α-cubene and (−)-cubebol.…”
Section: 218mentioning
confidence: 99%